More than words: Parent, Patient and Public Involvement perspectives on language used by clinical researchers in neonatal care - Moss,R; Lammons,W; Johnson,S; Ribas,R; Uthaya,S; Battersby,C; Cornelius,V; Babalis,D; Modi,N (Early Human Development, 2022)
In this qualitative study exploring parent views of information about research studies, we found they accepted uncertainty as justification, and that three key aspects of language - words, tone, and pace - influence parents' decision about their baby's inclusion. We recommend parents are routinely involved in developing information materials.